2013
DOI: 10.1111/tme.12022
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a massive transfusion protocol in the management of massive haemorrhage

Abstract: Although there has been a significant change in transfusion practice in MT patients using a MTR, no change in mortality could be documented using such a protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 21 publications
1
34
1
Order By: Relevance
“…Sinha et al's study of MTP use in a similar civilian setting reported a 29% overall mortality rate among their study cohort of trauma and non-trauma patients. (32) The difference in overall mortality rates between Sinha et al's study and our study could be due to the precocious analysis of our centre's MTP at 17 months. As MTP usage matures with time, compliance is likely to improve, resulting in improved mortality outcomes.…”
Section: Discussioncontrasting
confidence: 44%
“…Sinha et al's study of MTP use in a similar civilian setting reported a 29% overall mortality rate among their study cohort of trauma and non-trauma patients. (32) The difference in overall mortality rates between Sinha et al's study and our study could be due to the precocious analysis of our centre's MTP at 17 months. As MTP usage matures with time, compliance is likely to improve, resulting in improved mortality outcomes.…”
Section: Discussioncontrasting
confidence: 44%
“…Studies describing outcomes in patients requiring MT conducted in Australia are limited to single‐hospital studies of trauma patients . For example, Mitra et al .…”
Section: Introductionmentioning
confidence: 99%
“…This lack of clarity has arisen from the practice of excluding cases where an MTP has been activated for patients requiring little or no transfusion [4,18] and a general paucity of information about the size and composition of the denominator groups [3,19]. The only brief insights into this issue have been provided by Hendrickson et al [20] Morse et al [21] and Sinha et al [22] who, in their respective paediatric, adult non-trauma and mixed MTP groups, have all noted MTP activation can be followed by little or no transfusion.…”
Section: Discussionmentioning
confidence: 98%